2000
DOI: 10.1161/01.cir.102.12.1364
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of GR-II Stent and Palmaz-Schatz Stent for Elective Treatment of Coronary Stenoses

Abstract: for the GR-II Randomized Clinical Trial InvestigatorsBackground-This prospective multicenter randomized clinical trial was designed to evaluate the long-term angiographic and clinical outcomes of elective treatment with the GR-II stent compared with the Palmaz-Schatz (PS) stent in patients with coronary stenoses. Methods and Results-Seven hundred fifty-five patients with myocardial ischemia and de novo native coronary stenoses in 3-to 4-mm vessels were randomly assigned to the PS (375 patients) or the GR-II st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 15 publications
2
44
0
3
Order By: Relevance
“…Our data showed a 4.5-fold risk of complication (CI: 2.2-9.1) greater with filamentary stents, and a 2.4-fold risk of complication (CI: 1.2-4.6) greater with first-generation tubular stents. These findings are in accordance with those of previous studies showing a weaker radial strength of filamentary stents and the possibility of a greater prolapse of the plate between their rods, allowing greater residual stenoses and a greater thrombogenic substrate 22 . Although these models of prostheses are no longer being used clinically, these results emphasize the importance of the design and shape of the stent in the outcome of the procedure and may be important in the future, when the availability of stent coating This study was initiated in 1996, including filamentary and first-generation stents.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed a 4.5-fold risk of complication (CI: 2.2-9.1) greater with filamentary stents, and a 2.4-fold risk of complication (CI: 1.2-4.6) greater with first-generation tubular stents. These findings are in accordance with those of previous studies showing a weaker radial strength of filamentary stents and the possibility of a greater prolapse of the plate between their rods, allowing greater residual stenoses and a greater thrombogenic substrate 22 . Although these models of prostheses are no longer being used clinically, these results emphasize the importance of the design and shape of the stent in the outcome of the procedure and may be important in the future, when the availability of stent coating This study was initiated in 1996, including filamentary and first-generation stents.…”
Section: Discussionsupporting
confidence: 93%
“…WSSG, in practice stent oversizing to ensure maximum patency is more common [39]. Seo et al created models to investigate flow disturbances in 2D straight and curved vessels with Newtonian and non-Newtonian flow [35].…”
Section: Effect-based Researchmentioning
confidence: 99%
“…1,31 Bare metal stent trials and registries have demonstrated mean late losses varying from 0.6 to 1.2 mm. 5,6,26,27,[32][33][34][35] The RAVEL trial of the sirolimus-eluting Bx Velocity stent was the first randomized trial to report a stent with an average late loss well below the expected historical range, as well as its own control arm (in-stent late loss Ϫ0.01 mm active versus 0.80 mm control), which corresponded to a BAR rate of 0% for the active arm versus 26% in the control arm. 36 As the positive mean of any normal distribution is reduced enough so that its spread becomes significantly bounded by zero, it becomes right-skewed.…”
Section: Late Loss and Its Skewed Distribution For Dessmentioning
confidence: 99%